Collaborative innovation in sustainable fashion: A consumer-centric perspective on adoption and brand performance - Sasichakorn Wongsaichia; Teerapong Pienwisetkaew; Chavis Ketkaew (PLoS ONE, 2026)
Involving consumers in product ideation and development can generate innovations that better satisfy customer needs and, hence, are more likely to be adopted. Moreover, such customer-centric innovation processes reinforce the emotional as well as functional linkages between consumers and sustainable products, a dimension that is significantly more important than current collaboration at the firm level or in the supply chain for sustainability research. This study, therefore, explores how perceived collaborative innovation (PCI) affects perceived brand performance (PBP) in the sustainable fashion sector, particularly uncovering the key psychological mechanisms underlying how PCI affects consumer behavior. Specifically, this study reveals the mediating roles of the perceived benefits of sustainable fashion (PBSF) and consumer willingness to adopt sustainable fashion (CWASF) in the relationship between PCI and PBP. Using survey data of 602 Thai consumers (from an emerging economy), which can reflect the behavior of consumers in developing markets, and employing a Structural Equation Modeling (SEM) methodology, this study finds that PCI positively affects both PBSF and CWASF, leading to enhanced PBP. Moving beyond firm-level collaboration for sustainability by applying a consumer-centered perspective, the study introduces a framework that identifies the linkages between innovation perception, behavior, and brand performance. By demonstrating how collaborative innovation is a psychological driver of sustainable adoption and brand competitiveness, this study provides insights to help accelerate sustainability in the fashion industry, particularly in emerging markets.